Dietary acidifiers and nutritional value of soybean processing by-products for swine - Gaffield, Katelyn Nicole (Kansas State University, 2024)
A total of 8 experiments structured in 6 chapters were performed to evaluate the impacts of in-feed acidifiers in nursery and grow-finish diets, develop a phytase release curve, and assess the composition and nutritional value of soybean processing by-products in swine diets. Chapter 1 utilized 320 pigs to evaluate the effects on growth performance and bone characteristics of 12- to 24-kg nursery pigs and develop an aP release curve for Smizyme TS G5 2,500 included from 500 to 2,500 FTU/kg. Overall, pigs fed increasing phytase had increased average daily gain (ADG), average daily feed intake (ADFI), gain-to-feed ratio (G:F), and final weight. Additionally, pigs fed increasing phytase had increased bone ash weight, percentage bone ash, bone density, and bone P. The available P release curve generated for Smizyme TS G5 2,500 for percentage bone ash using data generated from three bones is: aP release, % = (0.228 × FTU/kg) ÷ (998.065 + FTU/kg). Chapter 2 utilized 4,618 pigs across three studies to evaluate different benzoic acid feeding strategies in nursery and finishing pig diets. Overall, pigs fed benzoic acid in post-weaning diets had improved growth performance but if removed from the diet in late nursery, pigs had decreased performance relative to those maintained on benzoic acid throughout the study. In finishing, inclusion of benzoic acid had inconsistent results with one study finding improvements in G:F while the other found a reduction in G:F. Chapter 3 utilized 2,560 pigs across two studies to evaluate the effects of increasing sodium diformate in both nursery and finishing pig diets. Overall, increasing sodium diformate has the potential to improve feed efficiency in the early nursey period but did not affect performance in the late nursery. Furthermore, feeding increasing sodium diformate improved ADG and increased ADFI after d 60 (~82 kg) in the finishing period, but carcass traits were not influenced. Chapter 4 provided a comprehensive literature review on soybean processing by-products and their use in swine and poultry diets. Chapter 5 encompassed an industry survey from 14 soybean plants across 8 production companies in the US to evaluate the composition and variation of soybean processing by-products. These data suggest soybean gums had a greater acid hydrolyzed fat content and decreased moisture and volatile matter percentage than soybean soapstocks. Notably, there was considerable variation in by-product composition between processing plants indicating differences in processing procedures or incoming soybean quality. Furthermore, when soybean by-products were added back to soybean meal, there was an increase in ether extract, but no effects on crude protein. Ultimately, soybean meal containing greater than approximately 1.6% ether extract on a dry matter basis likely contains soybean by-products. Chapter 6 utilized 350 pigs to evaluate the effects of soybean gums and soapstocks added back to soybean meal on nursery pig performance. Overall, adding soybean processing by-products such as soybean gums or soybean soapstocks had minimal effects on nursery pig growth performance. However, there is a potential for improved ADG and apparent total tract digestibility of dry matter when soybean meal containing added gums is included in the diet. The information generated evaluating a phytase release curve and the use of in-feed acidifiers in swine diets can be used by producers to help optimize efficient diet formulation. Furthermore, the information generated on the composition of soybean processing by-products and their use in swine diets allows for a better understanding of soybean meal quality across US soybean processing plants.
Keywords: Acidifiers; Phytase release curve; Soybean by-products; Soybean gums; Soybean soapstocks; Soybean meal quality